Young Generation Ready to Work: Communication Skills Enhancement Training Model to Attract Customers - Yuniorita Indah Handayani; Suwignyo Widagdo; Agustin H P (Trescode Green Organization, 2024)
The purpose of this study was to explore the impact of communication training on the skills of young people in Jember Regency, East Java, Indonesia. The method of this training activity used a qualitative approach by collecting data through in-depth interviews and observations during communication training conducted in Jember Regency, East Java, Indonesia. The results showed that the training was effective in improving participants' skills in public speaking, active listening, and communicating through digital media. Evaluation of participants showed consistent increases in self-confidence and the ability to convey ideas effectively. These findings emphasize the importance of investing in communication skills development as an integral part of individual development and social progress. The results of this study provide a strong foundation for the expansion and improvement of communication training programs in the future, with a focus on the integration of digital technology and adaptation to the diverse needs of participants.